Effect of Admixture on Freeze-thaw Damage of Sleeve Grouting Materials - WU Zhaoyue; ZHU Haiqing (Renmin Zhujiang)
This paper compares the physical and mechanical properties of sleeve grouting materials with different admixtures under freeze-thaw action by means of control variable method,studies the effects of different admixtures and different contents on the apparent morphology,mass loss and strength loss of sleeve grouting materials under freeze-thaw action,and further analyzes the change of species,quantity and morphology of hydration products in freeze-thaw cycle by SEM (scanning electron microscope).The results show that:After 120 freeze-thaw cycles,the mass loss of mortar specimens with admixtures is less than 2%,which is lagged compared with the compressive strength loss;Based on the gray correlation analysis,the impact of expansion agent on the mechanical properties of mortar specimens under different freeze-thaw cycles is the lowest.However,with the addition of defoaming agent,the physical and mechanical properties of mortar specimens are more sensitive to freeze-thaw damage,and the sensitivity will increase with the increase of defoaming agent contents;From the microstructure analysis,the addition of expansion agent can improve the stability of internal C-S-H gel system after freeze-thaw action.